Frequency of Measles in Children Younger than 9 Months Old - Nawaz, Asif; Khan, Muhammad Faizullah; Khan, Wajid; Abbasi, Vildan Zaheer; Ali, Ubaid (Indus Journal of Bioscience Research, 2025)
Background: Measles remains a significant public health concern, particularly in infants younger than 9 months who are often ineligible for routine vaccination in many settings. This age group faces a vulnerability window due to the rapid waning of maternal antibodies, leading to increased susceptibility amid global measles resurgence. Objective: To determine the frequency of measles and explore its association with sociodemographic factors and vaccination status among children younger than 9 months. Methods: A cross-sectional study was conducted with 111 children aged less than 9 months presenting at the department of Pediatrics, Ayub Teaching Hospital (MTI) Abbottabad during June 2024 to January 2025. Data were collected on age, gender, residence (urban/rural), mother’s education and profession, family monthly income, and infant vaccination status. Measles diagnosis was based on clinical criteria and/or laboratory confirmation. Frequency and percentage were calculated for categorical variables. Post-stratification chi-square tests were applied to assess associations, with p ≤ 0.05 considered statistically significant. Data analysis was performed using SPSS version 22. Results: The overall frequency of measles was 14 (12.61%). The study population comprised 48.65% males and 51.35% females, with 56.76% from urban areas. Median age was 4.0 months (IQR: 2.0–7.0). Vaccination coverage was 80.18%. Stratified analysis showed no statistically significant associations between measles occurrence and age subgroups, gender, residence, maternal education, profession, family income, or vaccination status (all p > 0.05), though a non-significant trend of higher frequency was noted in unvaccinated infants (22.7% vs. 10.1%). Conclusion: Measles affected 12.61% of children under 9 months in this study, highlighting persistent risk in early infancy despite relatively high vaccination coverage. The lack of significant sociodemographic associations may reflect sample size limitations. These findings support the need for strategies to bridge immunity gaps, such as supplementary immunization or earlier vaccination in high-burden settings, to reduce measles burden in this vulnerable group.